Analysis of growth and instability in rice: a district level study in Maharashtra, India - Mondal, Biswajit; Jambhulkar, NN; Paul, S; Pradhan, AK; Kumar, GAK (ORYZA-An International Journal of Rice, 2024)
Maharashtra state contributes 3.4% of rice area and 2.65% production of the country. Considering its importance in national rice basket, this study was undertaken to examine the growth rate and instability in area, production and yield of rice in Maharashtra state. The district wise data of rice have been collected from Directorate of Economics and Statistics, Ministry of Agriculture and Farmers Welfare, Government of India and from the online sources of the state departments during the period 1983-84 to 2019-20, which have been divided into five periods for analysis. Compound annual growth rate and Cuddy-Della Valle Instability index have been computed for the five periods. The districts have been classified into five class based on the classification of instability. These classes are very low instability, low instability, medium instability, high instability and very high instability. Growth rate ranges from -0.6 to 0.08 for area, -2.1 to 1.74 for production and -1.51 to 2.01 for yield. Highest and lowest growth rate for area, production and yield was recorded in period IV for different districts. The instability ranges from 1.79 to 4.39 for area; 5.02 to 18.18 for production and 5.26 to 15.88 for yield. Highest instability was observed in period IV and lowest instability in period I for area and period II for production and yield, respectively. None of the districts classified as very low instability for production and yield in different periods. More than fifty per cent districts were classified as low instability and medium instability for area, production and yield.